The Inventory of Leaf Beetles (Coleoptera: Chrysomelidae) from Soraya Research Station Leuser Ecosystem, Indonesia - Nuraini AR; Suwarno; Alia Rizki (Postgraduate, University of Mataram, 2025)
The Soraya Research Station is are search area which was originally a former forest concession area. The purpose of this study was to determine chrysomelid beetles found at the Soraya Research Stationin the Leuser Ecosystem, which was carried out using an exploratory method through direct observation of the object using the insect net at 60 points following an existing trail. This research was conducted in August 2020-February 2021. The results showed that the leaf beetles (Chrysomelidae) obtained were 37 species and 370 individuals, consisting of 6 subfamilies, namely Subfamily Galerucinae (17 species), Cassidinae (9 species), Criocerinae (7 species), Eumolpinae (2 species), Cryptocephalinae (1 species), and Altycinae (1 species). The index value of beetle diversity in forest habitats at the Soraya Research Station is categorized as moderate (2.85).